EVALUATION OF EFFICACY OF JALOUKAVACHARANA AND SIRAVYADHANA IN THE MANAGEMENT OF VATARAKTA: A COMPARATIVE STUDY - Rajeshwari; Deenaprakash Bharadwaj; Harshavardhana K (International Journal of Ayurveda and Pharma Research, 2020)
Vatarakta is the illness that exhibits different signs and symptoms based upon the Dosha, Utthana and Gambheera Avastha. Dietary habits and life style modalities play a major role in the causation of Vatarakta. Though various remedies are there to treat it, Raktamokshana is said to be an effective, and standard technique. Hence it is claimed to be an important affective tool in the management of Vatarakta. This study is undertaken to explore and compare the efficacy of Jaloukavacharana and Siravyadhana in Vatarakta. Randomized comparative clinical trial was adopted in this study. 40 subjects fulfilling diagnostic and inclusion criteria were selected and divided into two groups. The day on which the procedure was conducted was considered as first day of the trail. Follow up was on 8th & 15th day. Total duration of Study was 15 days. In both the group there is a significant improvement of subjective and objective symptoms except on Vaivarnya. The collected data is statistically analysed Jaloukavacharana is found to be more effective in the features Daha and Shopha. Siravydhana is more effective in Shoola and Vivarnya. Both the procedure shows equal effect on Sparshaasahatva. The overall results of Group A are 82.11% and Group B is 82.76%. Both the treatments are equally effective in Vatarakta. Hence alternative hypothesis H3 is proved. This simple and cost-effective treatments are painless do not require any anaesthesia. Hence it can be easily performed in OPD level on day-care basis.